Analisis Kelembagaan Model Agent-Principle Pada Petani Keramba Jaring Apung Di Waduk Cirata Jawa Barat - Maria Maghdalena Diana Widiastuti (Universitas Musamus, Merauke, Papua, 2015)
Cirata dam, a man made resource, included in the The Common Pool Resources (CPRs). Trend of CPRs are over use and produce externality. The impacts of these externalities are the mass death of fish in pondfish, sedimentation and the most important suistainability of dam. The objective of this study is to analyze appropriate institutional model as the CPRs dam management. Data analysis for institutional arrangement using Dolsak&Ostrom approach. The results showed that management of dam are low enforcement, high demand of dam product, no leading sector for collective action, and there is political interest. Institutional redesign suggests two scenarios: best-case scenario and the status quo. Best-case scenario such as the establishment of authority as the leading sector, which was given full authority, exceeds the administrative boundaries (Trans boundry regime) and supported by adequate human resource. The status quo is a condition that currently exists, but need improvements especially in conduct participatory rules, environmental conditions, arrange the resource user and law enforcement among user, increasing human resources, and holistic management.